Comparison of biopsy results of HPV 16/18 and non-16/18 HPV positive patients with a normal PAP test, a tertiary center experience - Koyuncu, Kazibe; Kurt, Mustafa; Sakin, Önder; Akalın, Emine Eda; Denizli, Ramazan; Öktem, Abdülmecit; Alan, Yasemin; Gökkaya, Mustafa (Journal of Surgery and Medicine, 2021)
Background/Aim: Optimal management for HPV positive and cytology negative patients remains a controversial issue. Immediate colposcopy is suggested for HPV 16/18 positive patients, whereas patients with non 16/18 HPV oncogenic virus positive are recommended to co-test after a year. In this study, we aim to compare the immediate colposcopic biopsy results between HPV 16/18 and non-16/18 HPV positive patients with cytology negative patients. Methods: In this prospective cross-sectional study, we included 1028 HPV positive and cytology negative patients who were screened for cervical cancer between January 2017 and 2019. Liquid based preparations were used for cytology samples (ThinPrep Pap Test). Cervical specimens were analyzed with Hybrid Capture for HPV types. Patients underwent colposcopic examination, biopsy procedure and endocervical curettage. Results: A total of 424 (41.2%) patients were HPV 16/18 positive, while 604 (58.8%) were non-16/18 oncologic HPV positive. Colposcopic biopsy results of the patients revealed that of the HPV 16/18 positive patients, 246 (23.9) had no dysplasia, 101 (9.8) had LGSIL and 77 (7.5%) had HGSIL. Among the non 16/18 positive patients, 422 (41.1%) had no dysplasia, 144 (14%) had LGSIL and 38 (3.7) had HGSIL. All patients were referred for endocervical curettage, which resulted as follows: Among HPV 16/18 patients, 384 (37.4%) had no dysplasia, 21 (2%) had LGSIL and 19 (1.8%) had HGSIL. Five hundred seventy-one non 16/18 positive patients had no dysplasia, 26 (2.5%) had LGSIL and 7 (0.7) had HGSIL. The comparison of colposcopic biopsy results of HPV 16/18 and non-16/18 HPV positive patients were different in terms of no dysplasia and HGSIL (P=0.001 and P=0.001, respectively), while LGSIL results were similar. The endocervical curettage biopsy results of the patients revealed a significant difference in HGSIL results (P=0.03). The two groups were similar with respect to reports of no dysplasia and LGSIL. Conclusion: Direct referral of the patients, who are expected to be lost to follow-up, could be convenient for non-16/18 HPV positive patients with negative cytology to reduce progression of cervical cancer and the psychological burden of HPV positivity.